1991
DOI: 10.2527/1991.6931151x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization and maturity of bromegrass on in situ ruminal digestion kinetics of fiber.

Abstract: Four ruminally cannulated, nonlactating Holstein cows (593 kg) were fed bromegrass hay diets within a 4 X 4 Latin square. Treatments were arranged factorially and consisted of bromegrass fertilized with 0 or 89 kg N/ha and harvested in the late-boot or full-head stage of maturity. Total tract digestibility of DM (57.6 vs 51.1%), NDF (68.8 vs 63.0%), ADF (51.1 vs 46.0%) and cellulose (63.4 vs 53.5%) decreased with increasing maturity (P less than .05). These forages also were placed in dacron bags for determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 13 publications
1
24
0
3
Order By: Relevance
“…yield and nitrogen concentration in the forage are increased. Increased water concentration and decreased soluble carbohydrates are commonly observed after nitrogen fertilization of grasses (Messman et al, 1991;Brink and Fairbrother, 1992).…”
Section: Foragesmentioning
confidence: 99%
See 1 more Smart Citation
“…yield and nitrogen concentration in the forage are increased. Increased water concentration and decreased soluble carbohydrates are commonly observed after nitrogen fertilization of grasses (Messman et al, 1991;Brink and Fairbrother, 1992).…”
Section: Foragesmentioning
confidence: 99%
“…Van Soest (1982) reported that as nitrogen fertilization increases lignin production, digestibility may be reduced. Others (Messman et al, 1991: Puoli et al, 1991 found that the rate of neutral detergent fiber digestion and with it animal feed intake was increased upon nitrogen fertilization. Nitrogen fertilization of forages was more likely to increase digestibility of warm-season grasses because of their lower nitrogen content as compared to cool-season grasses (George and Hall, 1983).…”
Section: Foragesmentioning
confidence: 99%
“…These general increases were related to the plant growing stage because as plant growth advanced cellulosic content increased (6,25). The decreases in NDF and ADF content on the sampling date of 3 July and after the beginning of August were related to the increasing contribution of legumes to the allowed forage because legumes always have lower NDF and ADF contents than grasses (26).…”
Section: Discussionmentioning
confidence: 99%
“…As the CP concentration decreases, the ADF and NDF contents increase together with the advancing plant maturity (Messman et al 1991;Lacefield et al 1999;Linn ve Martin 1999). In the ungrazed site, similar results with respect to CP, ADF and NDF contents can be attributed to plant maturity, whereas the unchanging CP content and increasing ADF and NDF contents in grazed area can be ascribed to the grazing effects.…”
Section: Discussionmentioning
confidence: 99%